The 100 : A Co-working Space in Kathmandu - Neupane, Rabindra; Basnet, Bhupindra Jung; Kandel, Madan (Nepal Journal of Multidisciplinary Research, 2026)
Background: This article is about co-working spaces and their roles in supporting start-up enterprises and other professionals provisioning various infrastructural and service components with affordable costs and greater flexibility for use. The objective of this article is to highlight the emerging concept of co-working spaces model to accommodate start-ups, corporate professionals, and other freelancers at their initial stages of business conception. This research will also help Nepalese investors understand and identify co-working space business opportunities. This article has specifically reviewed the contemporary role played by co-working spaces to support start-ups, freelancers, and digital nomads as well as presented the facilities available at “The 100” a privately owned pioneering co-working space in Kathmandu as the case study. Methods: This is a qualitative case study and has used a descriptive research design. Secondary as well as primary sources of data have been used to prepare this article. Primary data has been collected through observations and interviews with owners, managers, and some current clients of the selected co-working space. Secondary data has been collected in the form of research articles and reports on co-working spaces. The data gathered has been analyzed and presented in tables. The small quantity observations did not necessitate the use of statistical analysis. Results: The history of co-working space business model is no longer than two decades. The co-working space model is new in Nepal. Few countable co-working spaces are found is in operation in Kathmandu among which The 100 is one of the pioneering privately owned co-working space served approximately 500 clients in 3-year periods of its establishment. It has been offering infrastructures for office use including furniture, office rooms, meeting rooms, parking space, cafeteria service, internet, and office administration facilities in terms of flexible period and sharing basis. Office rooms are also available on non-sharing basis. Most of its member clients found joined due to their requisite of lower cost shared infrastructural facilities on a flexible use basis rather than for organizing events and need for networking, mentorship and coaching facilities. Conclusion: Globally, Co-working spaces are emerging forms of organization. Offering office infrastructures in sharing and use on a flexible basis has made it affordably attractive to start-ups. Similarly, co-working spaces are emerging also as an alternative to traditional forms of organizations for corporate and freelancers. In an absence of co-working spaces, the higher start-up costs may hinder nurturing start-up ideas. Similarly, the autonomous environment while working on creative ideas is its further attraction for corporate professionals and freelancers. Educated and skilled youths of Nepal are also getting attracted toward co-working space working environment. Novelty: To some extent, this article is expected to fulfill the gap existed in the dearth of academic research on co-working spaces and their roles in Nepal. This article will be useful to students, current and potential start-ups, corporate freelancers, nomads, and existing entrepreneurs to be acquainted with the possible use and benefit of co-working spaces in Nepal.